2010
DOI: 10.4161/chim.1.2.13147
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the earliest immune response to In Utero Hematopoietic Cellular Transplantation

Abstract: In Utero Hematopoietic Cellular Transplantation (IUHCT) is a promising intervention to treat a wide range of congenital disease. Through the presentation of donor cells to the immature immune system, mixed hematopoietic chimerism and donor-specific tolerance can be achieved. However, the failure of engraftment in prenatal recipients in which no immunodeficiency exists suggests the existence of a fetal immune barrier to transplantation. Although the possible barriers include effectors of the adaptive and innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Interestingly, there was no change in the distribution of the NKG2A + CD16 -, NKG2A + CD16 + , and NKG2A -CD16 + subsets during gestational weeks 15-22 ( Figure 2B and data not shown), suggesting that NK cell differentiation in the human fetus starts before gestational week 15 and is stable from gestational week 15-22. Similar to NKG2A, KIR expression is also associated with differentiation of CD56 dim NK cells in adults (25). To our knowledge, only one previous report has studied KIR expression on fetal NK cells, showing that they are expressed by a small subset of fetal liver NK cells at gestational week 14 (32). However, it is currently not known whether KIRs are expressed on NK cells in other fetal organs or whether KIR expression is associated with fetal NK cell differentiation, as is the case for adult PBNK cells.…”
Section: Figurementioning
confidence: 95%
“…Interestingly, there was no change in the distribution of the NKG2A + CD16 -, NKG2A + CD16 + , and NKG2A -CD16 + subsets during gestational weeks 15-22 ( Figure 2B and data not shown), suggesting that NK cell differentiation in the human fetus starts before gestational week 15 and is stable from gestational week 15-22. Similar to NKG2A, KIR expression is also associated with differentiation of CD56 dim NK cells in adults (25). To our knowledge, only one previous report has studied KIR expression on fetal NK cells, showing that they are expressed by a small subset of fetal liver NK cells at gestational week 14 (32). However, it is currently not known whether KIRs are expressed on NK cells in other fetal organs or whether KIR expression is associated with fetal NK cell differentiation, as is the case for adult PBNK cells.…”
Section: Figurementioning
confidence: 95%
“…The in vitro study of differentiating CD34+ hematopoietic progenitors indicates that CD94/NKG2A expression precedes the expression of HLA-specific KIR receptors by human NK cells ( Grzywacz et al, 2006 ). For this reason, we examined the expression of KIR receptors by early gestation human fetal NK cells and found that small subsets of human fetal NK cells express adult levels of KIR receptor by 10 weeks of gestation with more appreciable levels identified by 14 weeks gestation ( Alhajjat et al, 2010 ). A subsequent report by Ivarsson et al (2013) , demonstrated paradoxical hyporesponsivness to KIR-specific stimulation of second trimester human fetal NK cells.…”
Section: Early Gestation Human Fetal Nk Cells Possess the Capacity Fomentioning
confidence: 99%
“…However, a seminal report from our laboratory revealed that the potential for fetal NK cell allorecognition may begin in the first trimester of human development through the expression of killer immunoglobulin-like receptors (KIR) which are homologous to murine Ly49 receptors. Although the exact timing is unknown, we were able to demonstrate that only a handful of first trimester NK cells (10 weeks of gestation) expressed surface KIR whereas a significantly higher frequency of second trimester NK cells (14 weeks of gestation) expressed surface KIR (33). Similar to mice, interactions with MHC class Ia ligands appears to influence the KIR repertoire of mature human NK cells(34).…”
Section: Evidence Supporting a Fetal Immune Response To Iuhctmentioning
confidence: 77%